Investigating quiet quitting tendencies among nursing students: a descriptive study - Hümeyra Hançer Tok; Lütfiye Nur Uzun (BMC Nursing)
Abstract Background The phenomenon of “quiet quitting” performing only the minimum required duties without emotional investment—has gained prominence in both the workplace and educational settings. Aim This study was conducted to determine the quiet quitting levels of nursing students and to analyze how these levels vary according to gender, year of study, motivation for choosing the profession, and satisfaction with the department. Methods Descriptive and cross-sectional comparative design. The study was conducted with 210 nursing students selected through stratified sampling from a total population of 511. Data were collected via a personal information form and the Quiet Quitting Scale (16 items, 4 subscales). Non-parametric statistical tests (Mann-Whitney U, Kruskal-Wallis H, Spearman correlation) were employed using SPSS 26.0. Results The mean total score on the Quiet Quitting Scale was 50.04 ± 10.06, indicating a moderate level of disengagement. Male students reported significantly higher quiet quitting scores compared to females (p < 0.05). It was observed that self-protection subscale scores were higher among senior students (p < 0.05). Seniors scored higher on the self-protection subscale, suggesting increased risk awareness. Students who selected nursing due to internal motivation demonstrated lower levels of quiet quitting than those influenced by external factors (p < 0.05). A significant negative correlation was observed between satisfaction with nursing education and all dimensions of quiet quitting (p < 0.05). Conclusions Quiet quitting is notably present among nursing students and is influenced by gender, academic seniority, motivation for choosing the profession, and satisfaction with the educational experience. Curricular changes, active engagement strategies, and psychosocial support may help strengthen students’ professional identity and reduce passive disengagement. Mentorship programs, professional identity modules, and targeted support for students at higher risk of disengagement—including male students, those with low satisfaction, and those who chose nursing due to external motivations—could further address disengagement risks. These findings may inform international educational policies and contribute to the development of strategies to enhance student commitment and patient safety. Clinical trial number Not applicable.